Spinal Anesthesia Ambulation Time of Cervical Cancer Brachytherapy Outpatient Clinic: Comparison of 5 mg Hyperbaric Bupivacaine Fentanyl with 2,5 mg Hyperbaric Bupivacaine and 25 mcg Fentanyl - DM, Rica; Mafiana R; Zainal R; Bahar E (Journal of Anesthesiology and Clinical Research, 2024)
Introduction: Regional anesthetic techniques and local anesthesia have proven to be more effective than general anesthesia in the practice of ambulatory anesthesia. Spinal anesthesia is the technique of choice for ambulatory anesthesia in cervical cancer brachytherapy patients. Low-dose local anesthetics can speed up the ambulation time. This study aims to compare the ambulation time of low-dose spinal anesthesia with conventional doses. Fast ambulation time can speed up recovery time for patients, thereby reducing the patient's length of stay. Methods: This study was a double-blind, randomized controlled trial conducted in August – September 2022 at the Radiotherapy Installation of Dr. Mohammad Hoesin General Hospital (RSMH) Palembang. All cervical cancer patients undergoing brachytherapy in adults with ASA I-II physical status were included in the study sample. Samples will be randomized into two groups, namely a combination of hyperbaric bupivacaine 5 mg and fentanyl 25 mcg and a group of bupivacaine 2.5 mg and fentanyl 25 mcg. Patients with allergies, impaired motor function, spinal failure, block level not achieved, shock, apnea, respiratory depression, and experiencing pain during the procedure were excluded from the study. Results: Ambulation time in the hyperbaric bupivacaine 5 mg and 25 mcg fentanyl group was longer than the hyperbaric bupivacaine 2.5 mg and 25 mcg fentanyl (155.22 + 10.68 minutes versus 98.69 + 7.13 minutes) with a significance level of p<0.001. Spinal anesthetic drugs work in a dose-dependent manner. Increasing the dose will increase the duration of action of the spinal anesthetic. The only side effects found were hypotension and pruritus. Conclusion: Spinal anesthesia with hyperbaric bupivacaine 2.5 mg and fentanyl 25 mcg can accelerate the ambulation time of cervical cancer patients undergoing brachytherapy.